Rapport Building in Classroom: Strategies and Role in Learners’ Performance - Acharya, Resham (Tribhuvan University Journal, 2017)
Learners’ performance is mainly based on the quality of interaction between teachers and students. Such interaction between them is based on suitable environment created through mutual understanding and professional relationships between teachers and students. Despite this fact, this study has observed that many teachers are unaware about establishing mutual relationships and favourable environment for interaction with the students in their classes. Because of the authoritative behaviours of the teachers, students have issues in learning. This study has attempted to identify what students want to make favourable environment in class and role of rapport building for learners’ performance. The findings of the study reveal that the students had great desire of their teachers to have a sense of harmony with the students to help learners so as to enhance their performances.